PERAN GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS VIII SMP MELALUI PEMBELAJARAN AGAMA KATOLIK DAN BUDI PEKERTI - Br Purba, Emelda Winona; Tibo, Paulinus (Bahasa Indonesia Prima, 2023)
The Role of the Catholic Religious Education Teacher in Increasing Students' Interest in Class VIII Through Learning Catholic Religious Education and Characteristics at SMP RK Deli Murni Delitua. This research was conducted determine the role of Catholic religious education teachers in increasing interest in learning for Grade VIII students through learning Catholic religious education and morals. This type of research used is a qualitative method. The qualitative method was chosen because it can explore a problem in-depth and can explain in detail about a problem that occurs, starting from identifying a problem in-depth and explaining a problem that occurs, starting from identifying the problem to explaining the solution. The number of respondents in this study consisted of one Catholic religious education teacher and six students. The location of the research was at SMP RK Deli Murni Delitua. This Study used several techniques to collect the data observation, interviews, and documentation. The research subjects used were Catholic religious education teachers and class VIII students. The results of this study indicate that, firstly, the role of Catholic religious education teachers in this school is good. This can be seen from the students' increased interest in learning, and secondly, the students' interest in learning is good, 85% of students' interest in learning is high, and 15% is interested in low student learning.